The Effect of Ownership Structure, Sustainability Value, and Internationalization on Firm Value Mediated By Technical Efficiency in The Transportation and Logistics Industry In Indonesia - M. Arif Hernawan; Enny Haryanti; Herlina Herlina; Ika Utami Yulihapsari; Siti Nurhayati (Greenation Research & Yayasan Global Resarch National, 2026)
The transportation and logistics sector plays a strategic role in the Indonesian economy; however, firm value within this sector remains heterogeneous due to differences in technical efficiency and corporate strategies. Such variations indicate that ownership structure, degree of internationalization, and sustainability value may shape technical efficiency and, ultimately, firm value.This study aims to examine the effects of corporate ownership, internationalization, and sustainability value on firm value, with technical efficiency serving as a mediating variable. The study employs panel data regression and Sobel tests. Technical efficiency is measured using operational efficiency scores derived from a production-based approach, firm value is proxied by Tobin’s Q, internationalization is measured using the foreign assets to total assets ratio (FATA), sustainability value is measured by the ratio of corporate social responsibility expenditures to net income, and corporate ownership is measured by the proportion of institutional ownership. The sample consists of transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2014–2023.The empirical results indicate that corporate ownership and sustainability value positively affect technical efficiency, while internationalization has a negative effect on technical efficiency. Technical efficiency, in turn, positively influences firm value. Regarding direct effects on firm value, corporate ownership shows a positive but insignificant effect, internationalization has a positive and significant effect, and sustainability value has a negative effect. In terms of indirect effects through technical efficiency, corporate ownership and sustainability value positively influence firm value, whereas internationalization exerts a negative indirect effect.These findings contribute to the literature by highlighting the role of technical efficiency as a key mechanism linking ownership structure, internationalization, and sustainability value to firm value. From a managerial perspective, the study emphasizes the importance of optimizing technical efficiency in strategic decision-making within the transportation and logistics industry.